Uitdagings vir ’n reformatoriese benadering tot prediking in ’n postliterêre kommunikatiewe konteks - Wet, F. W. de (Koers, 2007)
Challenges posed to reformed preaching in a postliterary communicative context In this article the tension field is explored which manifests itself in the natural resistance of the reformed tradition against inclusion of visual elements in preaching on the one hand and the demands posed to the communicative structure of preaching in a postliterary context on the other hand. The need for practical theological theory formation with respect to two particular dimensions is explored, namely: effective and responsible integration of visual elements in the communicative structure of preaching in a postliterary context. The exploration of these two dimensions leads to the formulation of two challenges posed to reformed preaching: a) How may visual elements be introduced “effectively” in the communicative structure of preaching in a way that do not disturb the essential Word event of speaking God’s Word?; and b) How may visual elements be introduced “responsibly” in the communicative structure of preaching without reducing infinite elements to the realm of the finite on the one hand and abstractising life-changing elements to the realm of the unrealised? First steps in answering these challenges on a practice theoretical level will be given in a follow-up article.